1973
DOI: 10.1039/dt9730001475
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of π-cyclopentadienylcarbonylmetal halides in dimethyl sulphoxide and related solvents

Abstract: The principal product when solutions in dimethyl sulphoxide or pyridine of x-cyclopentadienylcarbonyimetal halides of Fe, Mo, and W are irradiated at long wavelengthsin the case of Fe (indicating loss of halogen) but appears to be [(X-C~H~)M(CO),CJ], for Mo and W; free cyclopentadiene and chloride ion are also produced in the case of Fe. The reactions do not proceed in non-polar solvents. At shorter wavelengths (A > 280 nm) the principal product in all cases is a dimeric species which could not be isolated, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…First, the energy positions of these bands have been determined to not be particularly solvent dependent (see Table ), which is typical behavior of d → d transitions. , Second, the molar absorptivities of these absorption bands are fairly low, consistent with orbitally forbidden transitions in organometallic complexes . Third, the earlier photochemical studies have demonstrated that these (η 5 -C 5 H 5 )Fe(CO) 2 X (X = halide) complexes undergo highly efficient CO dissociation following excitation at 366 and 458 nm 4b 1 Electronic absorption spectrum of (η 5 -C 5 H 5 )Fe(CO) 2 I in chloroform at room temperature.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…First, the energy positions of these bands have been determined to not be particularly solvent dependent (see Table ), which is typical behavior of d → d transitions. , Second, the molar absorptivities of these absorption bands are fairly low, consistent with orbitally forbidden transitions in organometallic complexes . Third, the earlier photochemical studies have demonstrated that these (η 5 -C 5 H 5 )Fe(CO) 2 X (X = halide) complexes undergo highly efficient CO dissociation following excitation at 366 and 458 nm 4b 1 Electronic absorption spectrum of (η 5 -C 5 H 5 )Fe(CO) 2 I in chloroform at room temperature.…”
Section: Resultsmentioning
confidence: 85%
“…In contrast, other studies have revealed that irradiation of (η 5 -C 5 H 5 )Fe(CO) 2 X can result in the formation of the dimer {[(η 5 -C 5 H 5 )Fe(CO) 2 ] 2 }, together with Fe 2+ , X - , and ferrocene, depending on experimental conditions. 3c,4c Metal−halide heterolysis and metal−metal-bonded dimer formation followed by subsequent disproportionation have been shown to be the main routes for the photochemical formation of ionic products from organometallic halide complexes. In the case of (η 5 -C 5 H 5 )Fe(CO) 2 I, the reaction involves the initial heterolysis of the Fe−I bond, a step which is recognized as being amine base assisted 4b…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The rhenium diazenido complexes (Re=N=N-R) have been extensively investigated since they were first reported in the early 1970s [92][93][94]. Because there are no stable isotopes of technetium, the structural investigation of the rhenium diazenido complexes [92][93][94][95][96][97][98][99][100] is more comprehensive than that of the technetium analogues at both macroscopic and tracer level [100][101][102][103][104][105][106][107][108][109]. However, a far greater number of reports have been published on 99m Tc compared to radiorhenium labeling of biomolecules with hynic.…”
Section: Hynicmentioning
confidence: 99%